Assessment of the salivary glucose as a non-invasive test for diabetic patients - Thapa, Kajol; Kunwar, Saroj; Thapa, Sonu; Phuyal, Asmita; Rupakheti, Sahil (International Journal Of Community Medicine And Public Health, 2019)
Background: Over the recent year there has been a startling rise in the number of people suffering from diabetes mellitus. Estimation of blood glucose levels has been an essential laboratory investigation for screening and monitoring of diabetes. Saliva is one of the secretions in human body whose collection is easy and non-invasive. Salivary glucose hence could serve as an easy and non-invasive tool. Methods: Institutional review committee of NHRC gave us permission to carry out this study. 105 subjects with Type 2 diabetes mellitus who attended the OPD at Star hospital, Sanepa, Lalitpur, Nepal and 106 healthy individuals were consented to participate in this study. Glucose was measured by the GOD-POD (Glucose oxidase peroxidase) methods using the semi-autoanalyser and salivary glucose was compared with corresponding blood glucose levels. Results: A significant positive correlation of fasting salivary glucose level and fasting blood glucose level was observed in healthy (r=0.241, p=0.001) and in diabetic patients (r=0.202, p=0.001). Conclusions: The study implies a potential for saliva in monitoring and screening of diabetes mellitus.